Evaluation of land use/land cover changes in Mekelle City, Ethiopia using Remote Sensing and GIS - Mary Tahir; Ekwal Imam; Tahir Hussain (Computational Ecology and Software, 2013)
Land use is a dynamic phenomenon that changes with time and space due to anthropogenic pressure and development. Evaluating the existing land use and its periodic change is useful for urban planners, policy makers and natural resource managers. Land use and land cover changes in Mekelle City, Ethiopia (north east Africa) over a period of 25 years was studied using remotely sensed data. Multi temporal satellite data of Landsat was used to map and monitor urban land use changes occurred during two point of time of 1985 and 2010. A pixel base supervised image classification was used to map land use land cover classes for maps of both time set. A positive changes of 200% was recorded in urban features of Mekelle, whereas, an area of 6 square km was added in grasslands. On the other hand a loss of 92.86% was estimated in bare land and all farm lands available in the area were converted into other feature and it declined from 3 square km to nil. Since forest land is protected so that no change in sparse forest was recorded.